Advances of Upconversion Nanoparticles for Molecular Imaging - Na Zhou; Jian Ni; Rong He (Nano Biomedicine and Engineering, 2013)
Molecular imaging is developing fast towards multi-modality and simultaneous therapy. For molecular imaging, upconversion nanoparticles (UCNPs), especially lanthanide-doped nanocrystals own obvious advantages such as low toxicity, large Stokes shifts, high resistance to photo-bleaching and photochemical degradation. Moreover, near infrared (NIR) excitation contributes to the auto-fluorescence minimization, a larger penetrating depth, and less harmfulness to cells compared with traditional ultraviolet (UV) excitation. On the other hand, the composites of UCNPs with biological target molecules exert superior performance, broadening their biological application scope from multi-modality imaging, to simultaneous drug delivery and targeted therapy. Herein, we review main advances of UCNPs applied to tumor multi-modality imaging and simultaneous therapy over the past few years, explore their application prospects, and discuss the concepts, issues, approaches, and challenges, with the aim of improving the application of UCNPs in biomedical imaging and therapy in near future.